Endoscopic Removal of Acute Traumatic Intracerebral Hemorrhage - I. M. Godkov; A. E. Talypov; V. V. Krylov; A. A. Grin; V. G. Dashyan; M. Yu. Savvin (Неотложная медицинская помощь, 2022)
ABSTRACT Nowadays surgical treatment of patients with traumatic intracranial hematoma (TICH) and injuries of the brain is a very actual problem in neurosurgery.The purpose of this work was to assess of the feasibility and safety of minimally invasive endoscopic removal of TICH.MATERIAL AND METHODS In the period of 2010–2019, 2734 operations were performed on patients with traumatic brain injury in the Sklifosovsky Research Institute. There were 334 patients with TICH and the CC/BC foci, that made 12.2% of all patients. The median of hematoma volume, that did not cause a loss of consciousness was 48 cm2, and in most of the patients the hematoma volume ranged 30–35 cm2. Local fibrinolysis of TICH was performed in 14 patients with the hematoma volume of 30–50 cm2 without brain dislocation and not causing the consciousness depression more severe than sopor.Endoscopic removal of TICH was performed in 4 men at mean age of 54.8 years within 18–36 hours after trauma. Three patients had depression of consciousness to obtundation (14 by Glasgow Outcome Scale (GCS)), and one patient was in clear consciousness. The volume of the dense part of the contusion foci in the pole-basal regions of the frontal and temporal lobes was 24–40 cm3.RESULTS Among patients with TICH operated on by using the traditional technique, postoperative lethality was 13%, good outcomes were seen in 41%, and 46% had neurological disorders of varying severity. While treating the patients with TICH by using the local fibrinolysis method, 1 patient died after surgery, a good outcome was seen in 8 of 14 patients, and neurological disorders persisted in 3 patients in the postoperative period.Radicality of surgery in patients operated on by using endoscopic technique averaged 76% ranging from 41% to 91%. There were no complications during surgery nor in post-operative period. Patients were discharged from hospital after 8-21 days.